(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This article dives into the concept of functional styles in the English language, focusing on their classification and linguistic features. Functional styles are essential in effective communication, as they adapt language to suit specific purposes and audiences. The paper explores scientific, official, journalistic, colloquial, and literary styles, analyzing their unique linguistic traits. Key features such as vocabulary choice, syntax, and stylistic devices are examined to demonstrate their role in shaping communication. This comprehensive study aims to underline the significance of functional styles in understanding stylistics and improving language use.